Room-temperature nanojoining of silver nanowires by graphene oxide for highly conductive flexible transparent electrodes. (22nd January 2023) - Ding, Su; Zhang, Shucheng; Yin, Tong; Zhang, He; Wang, Chenxi; Wang, Yong; Li, Qikun; Zhou, Nan; Su, Fengyu; Jiang, Zhi; Tan, Dan; Yang, Rusen
Abstract: Flexible transparent electrodes for touch panels, solar cells, and wearable electronics are in great demand in recent years, and the silver nanowire (AgNW) flexible transparent electrode (FTE) is among the top candidates due to its excellent light transmittance and flexibility and the highest conductivity of silver among all metals. However, the conductivity of an AgNWs network has long been limited by the large contact resistance. Here we show a room-temperature solution process to tackle the challenge by nanojoining AgNWs with two-dimensional graphene oxide (GO). The conductivity of the AgNWs network is improved 18 times due to the enhanced junctions between AgNWs by the coated GOs, and the AgNW-GO FTE exhibits a low sheet resistance of 23 Ohm sq −1 and 88% light transmittance. It is stable under high temperature and current and their flexibility is intact after 1000 cycles of bending. Measurements of a bifunctional electrochromic device shows the high performance of the AgNW-GO FTE as a FTE.